Confound it [large type] - Toussaint, Maggie (A dreamwalker mystery, 2019)
Dreamwalker, sheriff's consultant, and amateur sleuth Baxley Powell is called upon to help investigate a suspicious fire. A meth cook is dead, but the homicide investigation leads to more than a drug supply chain. Someone is pulling the strings behind the scenes, and unless Baxley stops the killer, the world will never be the same